Education in J.J. Rousseau: a methodological antecedent of competence based teaching - Sierra-Arizmendiarrieta, Beatriz; Pérez-Ferra, Miguel (Revista Complutense de Educación, 2014)
Taking into account the huge repercussion and influence that J.J. Rousseau has had on modern pedagogy, the recent tercentenary of his birth is a good opportunity to think about his outstanding relevance nowadays. This paper is a theoretical and educative research developed with an analytic and comparative hermeneutical method. The main objective is to show how some concepts of his philosophy of education have a great similarity with certain changes that the present competency based teaching is demanding, so it could be considered its methodological background. In order to achieve this objective this exposure has been divided in three parts. The first part is an analysis of Rousseau’s educational theory as developed in the first three books of the Emilio, in which one of the main themes is self experience-based learning, fostering self-sufficiency, curiosity and the motivation for learning. Rousseau proposed as a method the negative education, which requires, among other conditions, a constant monitoring of the learner by the tutor. In the second part, a brief summary of the most relevant changes and characteristics of competency-based teaching is developed, as well as its purpose. The student’s participation and activity are highlighted within their own learning process through the carrying out of tasks. The new educational model involves a radical change in the curriculum, in which it is highlighted the transformation of the methodology used in the classroom as well as the role of the teacher. Finally, the aim of the third part is to offer a comparative synthesis of both proposals grouping the parallelisms found in 4 topics: origin of the two models, its aims, methodology, and change in the teaching roles.